Clinician's guide to laboratory medicine : a practical approach - Desai, Samir P (Lexi-Comp, 2004)
Baylor College of Medicine, Houston, TX. Pocket-sized reference offers updated step-by-step approaches to lab test interpretation. Features more than 700 boxes, tables, and algorithms. Includes expanded sections on neurology, nephrology, rheumatology, and more. Also includes a complementary smaller pocket-sized version. Previous edition: c2002. Softcover.
Lexi-comp's clinician's guide series
Keywords: chemie, klinická chemie; laboratoře; Laboratories; příručky lékařské; Reference Books, Medical